Assessment of nylon 6, 6 nanofibre membrane for microalgae harvesting - Azizo, A.S. (American Institute of Physics Inc., 2017)
Pressure driven membrane processes have been proven suitable for the separation of microorganisms in many of biotechnical applications. In this paper, we report the preparation and characterization of a novel nylon 6, 6 nanofibers membranes and applied it for filtration of Chlorella vulgaris broth. Its performance is compared with a phase inverted polyvinylidene fluoride (PVDF) membrane, an established membrane material for this application. The tests on the filterability of both membranes and their harvesting efficiency were conducted. Results show that nanofiber membrane is more hydrophilic (contact angle of zero), and has 45 higher surface pore size and 20 surface pore population that contribute significantly into its higher clean water permeability (of 1018 and 493 l/m2hbar for nanofiber and PVDF membranes respectively). Filterability results show that nanofiber membrane has superior advantages over the phase inverted one: 2-5 times higher in productivity while maintaining similar rejection of 92. Those results were consistent for three independent filterability tests. This finding confirms the potential application of nanofiber membrane. However, further development with respect to improving its mechanical strength and its ability to be assembled into a membrane module should be critical to serve its promise in this particular application. © 2017 Author(s).